Aquatic macroinvertebrate biodiversity of lowland rural and urban ponds in Leicestershire - Matthew J. Hill (2015)
Ponds are common and abundant features in nearly all landscapes typical of European lowland landscapes yet research on freshwater biodiversity has traditionally focussed on larger waterbodies such as lakes and rivers. This has led to an increased need to understand and quantify the biodiversity associated with pond habitats to better inform the active conservation and management of these small waterbodies. This thesis examines the aquatic macroinvertebrate biodiversity (alpha, beta and gamma) and conservation value of 95 ponds in Leicestershire, UK, across a variety of urban and rural landscape types and at a range of spatial scales. In addition, the relative importance of local (physicochemical and biological) and spatial (connectivity) variables in structuring macroinvertebrate communities within ponds is investigated. At a regional scale, the greatest macroinvertebrate biodiversity and conservation value was recorded within meadow ponds compared to urban, agricultural and forest ponds. Spatially, ponds were highly physically and biologically heterogeneous. Temporally (seasonally), invertebrate communities were most dissimilar in meadow and agricultural ponds but assemblages were similar in urban and forest ponds. In urban landscapes, park ponds supported a greater diversity of invertebrates than other urban or garden ponds and typically had a greater conservation value. Garden ponds were the most taxon poor of those investigated. Perennial floodplain meadow ponds supported a greater biodiversity of invertebrates compared to ephemeral meadow ponds although conservation value was similar. Despite regular inundation from the River Soar, ephemeral ponds supported distinct communities compared to perennial meadow ponds. Aquatic macrophytes supported a higher diversity of taxa than other pond mesohabitats across all landscapes studied. Physicochemical factors were identified to be the dominant influence on macroinvertebrate assemblages although, a combination of local and spatial factors best explained the variation in community composition at a regional scale and for meadow ponds. Spatial factors were not identified to significantly influence urban pond communities. This study highlights the ecological importance and conservation value of ponds in rural and anthropogenically disturbed landscapes. Recognition of the significant contribution of ponds to freshwater biodiversity at regional and landscape scales is important for future conservation of pond habitats and will help focus and direct conservation strategies to where they are needed most.